Education for social citizenship : perceptions of teachers in the USA, Australia, England, Russia and China - Lee, W. O., 1954-; Fouts, Jeffrey T. (Hong Kong : Hong Kong University Press, 2005)
This volume, emerging from a cross-national study of teachers' perception of good citizenship, addresses two fundamental questions: What do teachers see as important in citizenship education? How do these perceptions facilitate or hinder the preparation of good citizens? While providing rich and useful data on the latest developments of citizenship education in various contexts, this book also offers an all-round review of concepts and arguments on the subject, as well as insightful comparative analyses of the findings emerged from the case studies. One encouraging conclusion drawn from these studies is that teachers across nations share similar goals and objectives that seem to have transcended cultural and political boundaries.
Cross-national citizenship study : background and methodology / W.O. Lee and Jeffrey T. Fouts -- Concepts of citizenship : from personal rights to social responsibility / Jeffrey T. Fouts and W.O. Lee -- Teachers' perceptions of citizenship in the United States / Carol Brown -- Teachers' perceptions of citizenship in Australia / Warren Prior -- Teachers' perceptions of citizenship in England / Ian Davies, Ian Gregory and Shirley C. Riley -- Teachers' perceptions of citizenship in Russia / Maria Jacobson Ellis and Carol Brown -- Teachers' perceptions of citizenship in China -- Cross-national comparisons and conclusions : teachers' perceptions towards social citizenship / W.O. Lee.
Includes bibliographical references (pages 263-281) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Citizenship -- Study and teaching; Civics -- Study and teaching; Citizenship -- Study and teaching -- Cross-cultural studies; Civics -- Study and teaching -- Cross-cultural studies; Citoyenneté -- Étude et enseignement -- Études transculturelles; Éducation à la citoyenneté -- Études transculturelles; Citoyenneté -- Étude et enseignement; Éducation à la citoyenneté.; EDUCATION -- Aims & Objectives; EDUCATION -- General; Citizenship -- Study and teaching; Civics -- Study and teaching; Cross-cultural studies